ADVOCACY EDUCATION AS AN EFFORT TO REALISE RIGHTS AND EMPOWER STUDENTS: A LITERATURE ANALYSIS OF PRINCIPLES, STRATEGIES, AND SOCIAL IMPLICATIONS - Fien Pongpalilu; Al-Amin (International Journal of Teaching and Learning, 2025)
Advocacy education is an approach that emphasises students' active involvement in fighting for their rights and empowering them as agents of change in the school environment. This study aims to analyse the principles, strategies and social implications of advocacy education based on a literature review. The results of the analysis show that the application of principles such as inclusivity, collaboration, and empowerment can increase student participation, build critical character, and foster a sense of social responsibility. Advocacy education strategies integrated in the curriculum, school policies and educational culture provide space for students to develop critical thinking, communication and leadership skills. In addition, advocacy education has a broad social impact, from creating an inclusive school environment to strengthening students' capacity to face challenges in society. However, the implementation of advocacy education also faces challenges such as cultural resistance and limited resources, so a joint commitment from all stakeholders is needed to optimise its benefits in realising a just and democratic education system.